Living With Hacktivism From Conflict to Symbiosis - Karagiannopoulos, Vasileios (Palgrave Studies in Cybercrime and Cybersecurity, 2018)
This book focuses on the phenomenon of hacktivism and how it has been dealt with up to now in the United States and the United Kingdom. After discussing the birth of the phenomenon and the various relevant groups, from Electronic Disturbance Theater to Anonymous, their philosophies and tactics, this timely and original work attempts to identify the positive and negative aspects hacktivism through an analysis of free speech and civil disobedience theory. Engaging in this process clarifies the dual nature of hacktivism, highlighting its potential for positive contributions to contemporary politics, whilst also demonstrating the risks and harms flowing from its controversial and legally ambiguous nature. Based on this hybrid nature of hacktivism, Karagiannopoulos proceeds to offer a critique of the current responses towards such practices and their potential for preserving the positive elements, whilst mitigating the risks and harms involved in such political practices. Finally, the study focuses on identifying an alternative, symbiotic rationale for responding to hacktivism, based on a cluster of micro-interventions moving away from the conflict-based criminal justice model and the potentially unjust and inefficacious results it entails. .